PENGARUH TINDAKAN KEPERAWATAN REDUKSI LUKA TEKAN TERHADAP PENURUNAN RISIKO LUKA TEKAN - Widodo, Wahyu; Rosa, Elsye Maria; Kurniasari, Novita (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Decubitus is a very serious problem especially for patients who hospitalized for long time with limited activity. Decubitus can increase the duration of hospital stay so that will increase the burden, especially the cost of hospitalization along with length of stay in hospital. This research of purpose to know the influences of nursing intervention to reduce pressure sore to reducing risk of pressure sore at RSU PKU Muhammadiyah Purworejo. This research design used â€œPre and post test without control group " with intervention reduction of risk pressure ulcer. This research is conducted in July 2016 with consecutive sampling method of 40 patients. Observations of pressure sore level on bed rest patiens done before and after treatment. The evaluation was done with wilcoxon ranks test and continued with cross tabulationÂ  for each treatment. The results showed a significant increase in risk of injury scores by 31 respondents, p = 0,000 <0.05. While the result of cross tabulation showed decreased risk of injured press on each level consisting of: high risk from 18 respondents down to 12 (66,7%) with baring and mass action. For the medium category there are 18 respondents 18 respondents dropped to 13 (72.1%) into low risk. As for the very high risk of 2 respondents who experienced a decrease in risk as much as 1 respondent while 1 other respondent remained, action at very high risk of wound care done according to grade I wound press. Likewise for low risk categories did not change, this is due to limited number of samples taken. The conclusion of this study is a decrease of risk pressure sore after applied preventive action for reduction of pressure sore in bed rest patients. The action apllied wound dressing, combination of massage and reposition, also health promotion.